An investigation into ESL readers metacognitive strategy awareness / Caroline Michael Umbak - Umbak, Caroline Michael (2009)
The main aim of this study was to investigate the level of metacognitive strategy awareness among a group ESL students. The study involved 19 ESL students reading a bachelor’s degree in Administrative Science at Universiti Teknologi MARA (UiTM) Sarawak. These students were selected based on convenience sample as they were readily available and were willing to participate in the research. The students were given a set of five-point Likert- scale Metacognitive Awareness Questionnaire (MAQ) to complete at the beginning of the investigation. The students were informed of the purposes and requirements of the survey, and they were asked to provide honest responses.